Robinson Crusoe - Defoe, Daniel; Chan, K. Y (Hong Kong Oxford university (China) press, 2005)
During one of his several adventurous voyages in the 1600s, an Englishman becomes the sole survivor of a shipwreck and lives for nearly thirty years on a deserted island
Keywords: English fiction